The substance that causes childbirth. Clinical and experimental study (Revista Española de Fisiología, 1946)
The dissosiation of the two decidual layers, is the single new fact that can be observed when the parturition is coming out. On admiting the destruction of a great number of decidual cells with absortion of cell integrant matters through an extensive and denudate surface and also a direct action in the uterous sensible zone by the friction that is produced between the two dissociated layers of the same decidua, we admit that the decidual matter perhaps would be capable of determinig the unchainig of the parturition. In order to verify this assertion we have preparated a aqueous extract of human decidua, obtained after the expulsion of foctal anexos; in order to prouve it in clinical and experimental, tests.As it seems of the facts observed by us, we conclude, in a first deduction, that on the end of pregnancy, the decidua loose some matters of colinergic and histamin like action and also possibly a matter or specific matters suitables for the coming-out of the parturition.